Academic procrastination among grade xi students in an islamic senior high school: the role of social media addiction - Yusuf Hidayatullah; Arri Handayani; Suhendri Suhendri (Indonesian Counselor Association (IKI), 2026)
Academic procrastination is the tendency to intentionally delay academic tasks despite awareness of the negative consequences involved. Social media addiction, arising from excessive and poorly regulated use, has been proposed as one factor associated with this behavior. This study examined the association between social media addiction and academic procrastination among 127 grade XI students (57 male, 70 female; aged 16–18 years) at an Islamic senior high school characterized by high everyday access to technology. A quantitative, cross-sectional correlational design was used; data were collected through a four-point Likert-scale questionnaire and analyzed using simple linear regression. Social media addiction was a significant positive predictor of academic procrastination (R = .785, R² = .616, p < .001), accounting for 61.6% of the variance in procrastination scores. These results indicate that, among the students surveyed, higher social media addiction is associated with a greater tendency to delay academic tasks; because the design is cross-sectional, this association should not be interpreted as establishing a causal, directional pathway.